Bioactive compounds in rice bran - Idris, Sakinah (2015)
Rice bran possesses several antioxidant and anticancer properties and can be a potential source of bioactive compounds to treat cancer and other diseases. The aims of this study were to compare different methods of drying rice bran, extraction of bioactive compounds present in rice bran, evaluation of the extracts for their antioxidant and anticancer activities and identification of compounds present in the extracts using gas chromatography-mass spectrometry (GC-MS). Rice bran was dried by oven-drying and freeze-drying. Dried rice bran was extracted by using 80 % methanol. Rice bran extract from freeze-drying method showed higher percentage of yield with 12.5 % and exhibited higher total phenolic content which 9.845 ± 1.47 8 mg/g. Rice bran extract from oven-drying method showed low percentage of yield with 9.0 % and exhibited lower total phenolic content with 2.2 ± 0.74 mg/g. Antioxidant activity of rice bran crude extract was evaluated using DPPH assay. Rice bran extract from freeze-drying method showed higher percentage of inhibition with 62.5 ± 0.01 % and lower IC 50 value of 76 μg/ml. Rice bran extract from oven-drying method showed lower percentage of inhibition of with 52.3± 0.01 % and IC50 value more than 500 μg/ml. For cytotoxicity assay, rice bran crude extract from both drying method showed high toxicity against MCF 7 cell line compared to the other cell lines. Glycerin and fatty acids were the major compounds detected by GC-MS. The minor compounds detected were phenolic compounds.